Characterization of a Triple Quantum Dot via an On‐chip Microwave Resonator. Issue 2 (17th December 2021) - Gu, Si‐Si; Wang, Bao‐Chuan; Chen, Ming‐Bo; Lin, Ting; Kang, Yuan; Li, Hai‐Ou; Cao, Gang; Guo, Guo‐Ping
Abstract: The hybrid circuit quantum electrodynamics architecture integrated quantum dots with a microwave resonator results in the creation of a controllable artificial system and enriches its physics through electron–photon interaction. In this study, a hybrid device is investigated, wherein a triple quantum dot (TQD) is dipole coupled with electric field of a superconducting quantum interference device array resonator. The quantum cellular automata (QCA) process of TQD, related to charge reconfiguration as a result of Coulomb interaction between each dot, is observed by probing reflectance of the resonator. The suppressed cavity reflectance signal of the QCA process may experimentally provide the evidence for the different measurement mechanism of the cavity from external electrometers like quantum point contact. Furthermore, on careful tuning of multiple energy level differences of the TQD to match the cavity photon frequency, four tunneling processes assisted by the absorption of the cavity photons occur simultaneously, contributing to "photon‐assisted" quadruple point. Consequently, these two specific phenomena are found to be closely dependent on the relationship between the various Coulomb energy in TQD and the cavity photon energy. The results are consistent with the theoretical model presented and imply that this hybrid system has the potential for investigating exotic many‐body effects and matter–light interaction. Abstract : The semiconductor triple quantum dot and microwave resonator hybrid system provides a promising platform for studying interacting many‐body models and matter–light interaction. This paper investigates special phenomena in this hybrid system, namely, quantum cellular automata and "photon‐assisted" quadruple point, which closely relates to the Coulomb interaction among multiple dots and the assistance of cavity photon.